2022
DOI: 10.1007/s12274-022-4385-4
|View full text |Cite
|
Sign up to set email alerts
|

Emerging prospects of protein/peptide-based nanoassemblies for drug delivery and vaccine development

Abstract: Proteins have been widely used in the biomedical field because of their well-defined architecture, accurate molecular weight, excellent biocompatibility and biodegradability, and easy-to-functionalization. Inspired by the wisdom of nature, increasing proteins/peptides that possess self-assembling capabilities have been explored and designed to generate nanoassemblies with unique structure and function, including spatially organized conformation, passive and active targeting, stimuli-responsiveness, and high st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 214 publications
0
5
0
Order By: Relevance
“…When treating the first, it is referred to as the "second illness" since it is so prevalent. 13 Due to their high cost and complexity, new noninvasive technologies of assessing iron storage in the body, such MRI or SQUID, are not widely used in impoverished nations like Pakistan. In our study, around 4/5 of the patients had serum iron levels over 2000 mg/ml, or approximately ten times the upper limit of normal.…”
Section: Discussionmentioning
confidence: 99%
“…When treating the first, it is referred to as the "second illness" since it is so prevalent. 13 Due to their high cost and complexity, new noninvasive technologies of assessing iron storage in the body, such MRI or SQUID, are not widely used in impoverished nations like Pakistan. In our study, around 4/5 of the patients had serum iron levels over 2000 mg/ml, or approximately ten times the upper limit of normal.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, some reviews with multiple perspectives have summarized the advancements of peptide-based nanoassemblies as well as the assembly mechanisms of peptides. 70,71 Interestingly, Sun et al reported the construction of nanocombination (PDC/P@HCuS) to develop a highly efficient tumor-targeting peptide drug. First, they engineered the in-/organic hybrid nanosystem by coupling the amphiphilic copolymer (PEDC) on the surface of copper sulfide (HCuS) nanoparticles to produce a new drug carrier and then loaded the cRGD-SMCC-DM-1-based peptide−drug conjugate as a targeted maytansinoid molecule to form PDC/P@HCuS (Figure 3).…”
Section: Lipophilic Naturementioning
confidence: 99%
“…These peptide-based nanoformulations are attractive for researchers because of several reasons: (i) Peptides favorably synthesized using the SPPS technique and thus could be modified at the molecular stage with customized properties; (ii) additional functionalization of peptide-nanoprobes could be introduced by conjugating exterior materials such as optical molecules, enzymes, and chemotherapeutics; and (iii) facile and costs effective self-assembly processes could bring into adaptation by tailoring the secondary structures (i.e., α-helices and β-sheets) of peptides. In recent years, some reviews with multiple perspectives have summarized the advancements of peptide-based nanoassemblies as well as the assembly mechanisms of peptides. , …”
Section: Strategies To Improve the Chemical And Enzymatic Stability O...mentioning
confidence: 99%
“…This prodrug molecule can self-assemble into a hydrogel in aqueous solution. Liu et al 135 and Elsawy et al 136 also demonstrated that hydrogel-based local drug delivery carriers have the potential to improve drug efficacy and reduce off-target toxicity for locally targeted tumors.…”
Section: Drug Releasementioning
confidence: 99%